Permainan Edukatif (Engkle Kalimat) Dalam Meningkatkan Kemampuan Membaca Siswa Kelas III SDN Sukamanah 02 Kec. Jasinga, Kab. Bogor - Gisty Awaliah; Rahmi Alendra Yusiyaka (Peneliti.net, 2022)
Reading interest in elementary school students is still very low, indicated by students who do not know letters and cannot read, because PTM has just been implemented in September and it turns out that almost 80% of third grade students cannot read, so students as parties from outside the school will starting to get used to carrying out the student literacy movement by doing 15 minutes of reading before starting learning accompanied by students and teachers. Literacy activities will also be carried out every week using educational games so that students are enthusiastic about participating in these activities. Reading ability in elementary school in grade III is low because of the impact of Distance Learning, so this study aims to improve the reading ability of grade III students at SD Negeri Sukamanah 02. The data obtained used interview, observation and documentation techniques. The results showed that improving the reading learning process with educational games (engkle sentences) could increase the reading interest of third graders at SD Negeri Sukamanah 02.